2009
DOI: 10.1021/ol802970g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Formal Homo-Nazarov Cyclization

Abstract: The first catalytic method for the cyclization of vinyl-cyclopropyl ketones (formal homo-Nazarov reaction) is reported. Starting from activated cyclopropanes, heterocyclic and carbocyclic compounds were obtained under mild conditions using Brønsted acid catalysts. Preliminary investigation of the reaction mechanism indicated a stepwise process.Carbocyclic and heterocyclic scaffolds occupy a privileged position in both natural products and pharmaceuticals. 1 Consequently, the development of cyclization and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 35 publications
(35 reference statements)
1
44
0
1
Order By: Relevance
“…Nevertheless, our preliminary investigations showed that the cyclization of vinyl cyclopropyl ketones was most probably a stepwise process via carbocationic intermediates, and therefore best described as a formal homo-Nazarov process. 17 For the reaction to proceed under mild conditions it was necessary to use a DA cyclopropane, whereas an electron-rich aryl substituent was especially successful (Scheme 9, B). At this point, we wondered if a DA aminocyclopropane could be used in the formal homo-Nazarov process.…”
Section: Cyclizations With Non-activated Aminocyclopropanesmentioning
confidence: 99%
“…Nevertheless, our preliminary investigations showed that the cyclization of vinyl cyclopropyl ketones was most probably a stepwise process via carbocationic intermediates, and therefore best described as a formal homo-Nazarov process. 17 For the reaction to proceed under mild conditions it was necessary to use a DA cyclopropane, whereas an electron-rich aryl substituent was especially successful (Scheme 9, B). At this point, we wondered if a DA aminocyclopropane could be used in the formal homo-Nazarov process.…”
Section: Cyclizations With Non-activated Aminocyclopropanesmentioning
confidence: 99%
“…[14] We de veloped the first catalytic homoNazarov reaction of crosspolarized substrates bearing an electronrich aromatic ring on the cyclopropane and a heteroatom on the double bond (Scheme 6). [15] In view of applications in the synthesis of natural products, we wondered if a ni trogen heteroatom could also play the role of activating group on the cyclopropane. Such intermediates could in principle give a general entry to the aspidosperma class of natural products, such as aspidospermi dine (14) (Scheme 7).…”
Section: Cyclization Reactions Of Activated Cyclopropanesmentioning
confidence: 99%
“…Furthermore, the Cbz group is easily removed under mild conditions. To our delight, the cyclization worked well under our previously developed conditions (20 mol % toluenesulfonic acid in acetonitrile) 10 and 74% yield of cyclized product was obtained. Careful NMR analysis of the crude mixture revealed a 1.6:1 mixture of C3 (10) and N1 (11) cyclization products.…”
mentioning
confidence: 93%